Personality rights and the (Im)possibility of using artificial intelligence in military police work: legal and philosophical reflections in light of legal theory and PL 2338/2023 - Almeida, Fernando Rodrigues de; Andrade, Rodrigo dos Santos; Souza, Guilherme Magalhães de (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 41 No especial (2025): Os Direitos da Personalidade e seus Reflexos na Pós-Modernidade, 2025)
This article analyses the debate surrounding the (im)possibility of using robots with artificial intelligence in the work environment of Brazilian military police officers, based on Federal Bill PL 2338/2023 and its relation to Personality Rights. The research examines the legal, social, and psychological impacts of these technologies in policing, considering the potential consequences of automation for the dignity, autonomy, and psychological integrity of security agents. To support this analysis, the study relies on Legal Theory, integrating Hegel’s conception of the State as a guarantor of freedom and ethical life (Sittlichkeit) with Foucault’s critique of disciplinary power and biopolitics. The discussion includes the impact of artificial intelligence on the precarisation of police work, the potential for surveillance through the digital panopticon, and the regulatory challenges within the Brazilian legal framework. The research employs a deductive method, with a qualitative approach, based on a bibliographical review of philosophical, legal, and regulatory texts. The findings indicate that the absence of clear regulatory guidelines regarding artificial intelligence in policing may compromise Personality Rights, exacerbating inequalities and increasing the risks of algorithmic discrimination. The study concludes that the regulation of these technologies must be based on a robust legal framework, ensuring that technological innovation is balanced with the protection of human dignity and social justice, in accordance with the foundations of Legal Theory.